Chemical and immunological features of pleural effusions: comparison between rheumatoid arthritis and other diseases. - Pettersson, T (1982)
The value of determination of pleural fluid glucose, pH, lactic dehydrogenase, IgG, IgA, IgM, C3, C4, anti-IgG antibody, and hydroxyproline in distinguishing between pleural effusions caused by rheumatoid arthritis (RA) and those resulting from other diseases was studied. The series comprised seven patients with RA and 115 patients with other diseases including systemic lupus erythematosus, tuberculosis, malignant disease, empyema, pneumonia, congestive heart failure, and nonspecific pleural effusion. The low glucose concentration, the low pH and the low C4 level in rheumatoid pleural effusion were the most valuable diagnostic findings. The presence of anti-IgG antibody in pleural fluid was not specific for RA. The concentration of hydroxyproline in pleural fluid and the pleural fluid-to-plasma hydroxyproline ratio were significantly higher in RA than in tuberculosis and malignant disease. The results support the view that local metabolic and immunological phenomena as well as a high turnover of collagen occur in the pleural cavity in RA.